Prevalence and clinical association of MET gene overexpression and amplification in patients with NSCLC: Results from the European Thoracic Oncology Platform (ETOP) Lungscape project. (September 2017) - Bubendorf, Lukas; Dafni, Urania; Schöbel, Martin; Finn, Stephen P.; Tischler, Verena; Sejda, Aleksandra; Marchetti, Antonio; Thunnissen, Erik; Verbeken, Eric K.; Warth, Arne; Sansano, Irene; Cheney, Richard; et al.
Highlights: This was a cohort study of surgically resected, stage I–III NSCLC cases from 17 centers. IHC MET overexpression was 23.8% and SISH MET amplification 4.6%, with significant correlation between them. MET IHC positivity rate varied highly between centers. Five MET ex14 cases were detected in a 'MET+ enriched' cohort of 182 cases (4 among 88 adenocarcinomas). Abstract: Introduction: In a well-defined NSCLC cohort of the ETOP Lungscape program, we explored the epidemiology of IHC MET overexpression and amplification, their inter-correlation, and their association to outcome. Methods: Resected NSCLC were assessed for MET gene copy number (GCN) and expression using silver in-situ hybridization (SISH) and immunohistochemistry (IHC) on TMAs in a multicenter setting. MET amplification was defined as MET/centromere ratio ≥ 2 (with average MET GCN ≥ 4), high MET GCN as CGN ≥ 5 and MET IHC+ as ≥2+ intensity in ≥50% of tumor cells. A total of 182 MET IHC+ and EGFR/KRAS WT tumors were analyzed for MET ex14 skipping mutation. Results: MET IHC+ was found in 23.8% of 2432 patients, significantly associated with female gender, small tumor size, and adenocarcinoma histology. We observed a high inter-laboratory variability in IHC and SISH analysis. MET amplification prevailed in 4.6% and MET GCN ≥ 5 in 4.1% of 1572 patients. MET amplification and MET GCN ≥ 5 were not significantly associated with any tumor characteristics or stage. Both were significantly associated with IHC MET positivity (p < 0.001). MET ex14 skipping mutation prevailed in 5 of 182 (2.7%) MET IHC+ WT EGFR/KRAS NSCLC, 4 of which within the 88 adenocarcinomas (4.5%). No association of IHC MET overexpression, SISH MET amplification or high MET GCN was found with OS, RFS or TTR. Conclusion: MET overexpression is found in 23.8% of surgically resected NSCLC. MET amplification prevails in 4.6% and is associated with MET overexpression. Both have no influence on prognosis. The large inter-laboratory variability in IHC highlights the challenge of MET IHC analysis in routine practice.